LES CORDOPHONES DU CONGO BELGE ET DU RUANDA-URUNDI by J. S. LAURENTY, 2 vols, 4to. paperback. Vol. I, text with 122 line drawings, 230 pp.; Vol. II, 37 plates and 5 maps. Annales du Musée Royal du Congo Beige, Tervuren, Belgium, 1960. - Basil, Brother (International Library of African Music, 1961)
pages: 110-111
Keywords: African Music